Antioxidant and Cytotoxic Activities of Lactic Acid Bacteria on Colorectal Cancer WiDr Cell Line - Wisnuwardhani, Popi Hadi; Ningrum, Ratih Asmana; Mustopa, Apon Zaenal; Vanggi, Leggina Rezzy; Kusdianawati, Kusdianawati Kusdianawati (Indonesian Society for Cancer Chemoprevention, 2021)
Colorectal cancer (CRC) is one of the leading causes of cancer and cancer-related deaths worldwide. Lactic acid bacteria (LAB) are bacteria that have potential activity as an inhibitor of the growth of colorectal cancer, and also has been widely used and was very useful for consumption. In our previous study, we isolated various LAB from Indonesian traditional fermented food. This study aims to determine the potential of LAB as an anticancer agent by determining the antioxidant activity and cytotoxicity assay of colon cancer in the WiDr cell line. This study used extracellular extract of various LAB. We use the Diphenylpicrylhydrazyl (DPPH) method to determine the antioxidant activity and 3-(4,5'dimethylihiazol-2-yl),2.5-di-phenyl-relrrzolium bromid (MTT) assay to study cytotoxicity activity. The viability cell staining also applied to detect unviable cells. The results informed that the highest antioxidant activity was shown by S.34 LAB with 81% activity. The S.34 also showed cytotoxicity activity with 73% of WiDr viable cell at a concentration of 200 μg/mL of LAB extract. Based on the results of the study, it can be concluded that the S.34 LAB from Bekasam may inhibit the proliferation of WiDr cell lines and It had the highest antioxidant activity comparing to other LAB samples.Keywords: Lactic Acid Bacteria, colorectal cancer, anticancer, antioxidant, WiDr cells.